Edukasi Remaja Rentan Terkena HIV/AIDS Akibat Perilaku dan Perkembangan Emosional yang Tidak Tertata - Ningsih, Hasrun; Ismiati, Ismiati; Pratiwi, Baiq Reni; Khairani, Fuji; Sustiyani, Elly (Jurnal Peduli Masyarakat, 2023)
Community Service is an activity that aims to help the community in several activities without expecting rewards in any form. In general, this program is designed by various universities in Indonesia to make a real contribution to the nation, especially in developing the welfare and progress of the Indonesian nation. Methods: lectures and using leaflets and billboards containing pictures about the dangers and effects of HIV/AIDS. Result: This Community Service Activity is an effort to prevent the increase in HIV / AIDS, In this activity, Knowledge in adolescents will be quickly absorbed if given a stimulus as in this service activity by showing pictures of how the dangers of free sex behavior that can result in HIV / AIDS, Students are very enthusiastic about the knowledge and information of the sciences conveyed by the Extension Team so that it can be said to increase the knowledge of adolescents about HIV / AIDS. The solution offered by the PKM team from this program is the preparation of material delivery (education) and how to prevent HIV/AIDS for adolescents from contracting this deadly disease.